ANALISIS IMPLEMENTASI KEBIJAKAN POLDA LAMPUNG DALAM PENGEMBANGAN SUMBER DAYA MANUSIA (Studi Pada Markas Polisi Daerah Lampung) - Ahmad Mofian (e-JKPP, 2016)
Reform of the institutions of the state apparatus as well as the Indonesian National Police (Polri) can not be held separately from other state agencies. In practice, human resource development is needed in view of the function of the police is very important in the midst of society. Associated with the development of human resources, Lampung Regional Police or abbreviated as Lampung Police continues to make improvements related to the improvement and optimization of the performance of the Regional Police.The research method used is the analysis of qualitative data. Where researchers work directly spaciousness to obtain data from the beginning to the end of the study. Sources and types of data used are primary data and secondary data. Methods of data collection by library research, observation, interviews and documentation.The results of the study explained that the implementation of policies Lampung Police in human resource development is already quite good, but the awareness and interest of members of Lampung Police still need to be improved related to human resource development in Lampung Police.Keywords: The policy implementation Polda Lampung, Human Resources Development.